Magnetic beads–assisted fluorescence aptasensing approach based on dual DNA tweezers for detection of ochratoxin A and fumonisin B1 in wine and corn - Qu, Chenling; Zhao, Luyang; He, Xing; Yu, Songcheng; Wei, Min (Analytical and bioanalytical chemistry, 2021)
A magnetic beads (MBs)–assisted fluorescence aptasensing approach based on dual DNA tweezers and magnetic separation was established for the detection of ochratoxin A (OTA) and fumonisin B 1 (FB 1 ). A dual DNA tweezers structure with four ends linked with fluorophores (FAM, ROX) and quenchers (BHQ 1 , BHQ 2 ) was designed, and produced the high initial fluorescence signals because of the long spatial distance between FAM and BHQ 1 , ROX, and BHQ 2 . Bio-aptamer/anti-aptamer of OTA and bio-aptamer/anti-aptamer of FB 1 were respectively annealed to form dsDNA, and immobilized to MBs coated with streptavidin (SA). With the existence of OTA and FB 1 , OTA and FB 1 preferentially bound with their respective bio-aptamers, which made anti-aptamers dissociate from dsDNA coupled on MBs. After magnetic separation, the dissociated anti-aptamers reacted with dual DNA tweezers, respectively, which made DNA tweezers close and the fluorescence was quenched. The linear ranges of approach for OTA and FB 1 detection were 0.05–20 ng/mL and 0.1–40 ng/mL, respectively. The limit of detection for OTA and FB 1 was 0.029 ng/mL and 0.061 ng/mL. The prepared MBs-assisted fluorescence aptasensing approach was applied to detect OTA and FB 1 in spiked red wine and corn samples, which showed good recoveries between 92 and 106%.